Evaluasi Kecepatan Lalu Lintas dan Fasilitas Jalan (Studi Kasus: Jl. Raya Karang Anyar – Jl. PTPN VII Trikora Lampung Selatan) - Galuh Pramita (Jurnal Serambi Engineering, 2024)
The Karang Anyar Road - PTPN VII Trikora Anyar Road in South Lampung does not have adequate facilities. There are no street lights and road markings are not clearly visible. This situation can endanger the safety of drivers. In this study, the evaluation conducted includes evaluation of traffic speed and adequacy of road facilities to minimise traffic accidents. The research method broadly includes preparation, literature review and site identification, followed by conducting the research, namely speed and road facility adequacy surveys. The results of the survey on signs and markings in the current conditions show a lack of road facilities, including the absence of traffic lights and road control and safety devices. Other facilities such as warning signs are present. Street lighting is still inadequate as it is only present at a few points and does not provide adequate lighting for the Karang Anyar Road - PTPN VII Trikora Anyar Road in South Lampung. Vehicle speed shows that the speeds of vehicles passing through Karang Anyar Road are as follows: Light Vehicles (LV) at 27.69 km/h, Heavy Vehicles (HV) at 20.69 km/h, and Motorcycles (MC) at 40.67 km/h.